An application of the analytic hierarchy process method in farmland appraisal - Aznar Bellver, J.; Caballer Mellado, V. (Spanish Journal of Agricultural Research, 2005)
This paper applies a multi-criteria methodology to farmland appraisal known as the analytic hierarchy process (AHP). This methodology is especially useful when there is partial information and/or qualitative variables are used or when quantitative variables are used but the professional does not have access to their quantification. This context presents difficulties when applying conventional farmland appraisal methods. Likewise, the application of the analytic hierarchy process to the field of farmland appraisal is an advance with respect to previous studies on the application of multi-criteria methods in which only quantitative variables have been used.